Empirical Analysis of Structural Income Changes in Commercial Banks: A Case of Pakistan - Ramla Sadiq; Tahseen Mohsan Khan; Noman Arshed (The Lahore Journal of Business)
The primary purpose of this study was to conduct an exploratory and explanatory analysis to determine the impact of structural income on performance of the all commercial banks in Pakistan from 2008 to 2015. It aimed to establish the theory on dual impact of income diversification and ownership on bank performance in a developing economy. This population was divided into two categories - ownership mode characterized into conventional and Islamic banks and category mode characterized into five proportions of non-markup and mark up income structures. The divisions were analyzed on the basis of change in assets and equity and gross income, using a non-linear approach. This approach ensured robustness of analysis and clearer outcomes regarding strategic approaches in this sector. Ownership mode finding suggested conventional banks tilt towards non-markup income significantly for asset and gross income base increase and Islamic banks insignificantly towards markup income. Our findings also showed that conventional banks lead Islamic banks, and banks with nonmarkup income between 30%-40% lead other bank categories in terms of managing profitability. Islamic banks are ahead of conventional banks, and category1 banks with non-markup income above 50% are ahead of all other categories in terms of utilization of funds.